Employment protection legislation tested by the economic crisis. A global review of the regulation of collective dismissals for economic reasons - Muller, Angelika (Geneva, 2011)
"The brief identifies the principal elements of the regulation of collective dismissals for economic reasons in over 125 countries, together with reforms introduced between 2008 and 2011. It considers the national legislative provisions regulating the seven subject areas of the employment protection legislation (EPL)."